Uji Kir Kelayakan Kendaraan Bermotor Menggunakan Metode Certainty Factor - Angger Kurniawan; Budi Serasi Ginting; Imeldawaty Gultom (Yayasan Kita Menulis, 2022)
Motor vehicle testing is a series of activities to test and inspect parts on motorized vehicles. Vehicle testing that still uses a manual system makes the testing service process take a long time and there are often delays in vehicle testing. Therefore, a system is needed to simplify and speed up the vehicle testing process. Based on this, this research is intended to create a motor vehicle testing information system that can assist officers in carrying out vehicle testing services. From the results of the research conducted, it greatly increases knowledge and insight, by collecting data relating to the motor vehicle feasibility test. The PHP programming language and MySQL database can be built into a system for testing the feasibility of motorized vehicles using the Certainty Factor method. Based on the data on the motor vehicle assessment criteria, it can be tested for the feasibility of motorized vehicles using the Certainty method. From the results of calculations using the Certainty Factor method and based on the weight of each criterion, it can be analyzed from the calculations that have been carried out with the results of the motor vehicle test passing with a confidence level of 97.10%, conditional passing with a confidence level of 95.84%, and not passing with a level of confidence. confidence 94.75%. Thus, the above vehicle is declared to have passed the kir test with a confidence level of 97.10%.